THE IMPACT OF HIGH-PROTEIN DIET ON GUT AND METABOLIC HORMONES: A SYSTEMATIC LITERATURE REVIEW 2021-2025 - Świerk, Karolina; Podkościelny, Damian; Machulski, Wojciech; Ciarkowska, Martyna; Makulski, Jan; Franczyk, Kamil; Gierasimiuk, Maria; Gorski, Michal; Januszkiewicz, Adam; Januszkiewicz, Wiktoria (International Journal of Innovative Technologies in Social Science, 2025)
Objective: This systematic literature review evaluates the impact of high-protein diets on key gut and metabolic hormones in humans, emphasizing GLP-1, glucagon, insulin, ghrelin, and leptin.Methods: A systematic review of scientific literature from 2021-2025 was conducted. Randomized controlled trials (RCTs), crossover studies, and meta-analyses examining effects of high-protein diets (≥25-30% energy from protein) on hormonal and metabolic parameters were analyzed in healthy individuals and those with obesity, type 2 diabetes, and other metabolic conditions.Results: High-protein diets consistently stimulated GLP-1 secretion, with active GLP-1 increasing 87-156% after a single meal compared to controls. Whey protein demonstrated strong insulinotropic properties, with optimal effects at 15-55g consumed 15-30 minutes pre-meal. Significant postprandial glycemia reduction was observed (mean -1.4 mmol/L; up to -2.0 mmol/L in T2DM individuals) alongside improved insulin sensitivity indices (HOMA-IR, Matsuda index). Increased glucagon/insulin ratio promoted fat oxidation and preferential adipose tissue loss while preserving lean mass. High-protein diets suppressed ghrelin, modulated leptin, and enhanced satiety, though appetite hormone effects were more complex than incretin responses. Long-term interventions (6-12 months) demonstrated visceral and hepatic fat reduction (mean -42% IHL), improved lipid profiles, and beneficial gut microbiota changes.Conclusions: High-protein diets beneficially impact gut and metabolic hormones through incretin stimulation, glucagon/insulin ratio modulation, improved insulin sensitivity, and appetite hormone regulation. These effects translate to clinically significant metabolic improvements, particularly in individuals with type 2 diabetes and obesity. Optimal dosing (25-35% energy from protein, 1.2-2.0 g/kg/day) and timing (preload 15-30 minutes pre-meal) maximize metabolic benefits, indicating potential for effective dietary intervention in preventing and treating metabolic disorders.